Examen especial de Gestión Al Talento Humano del distrito 14d04 Gualaquiza San Juan Bosco - educación, del cantón Gualaquiza de la provincia de Morona Santiago, en el periodo 2014 - Araujo Ochoa, Kathia Alexandra (2016)
This research was developed considering the rules and procedures of the Organic Law of Intercultural Education and its General Regulations, the provisions of Regulation of the Ministry of Education was considered. Conducting a special examination to Talent yielded an institutional methodology and strategic vision, examined and evaluated the activities carried out in order to determine the efficiency and effectiveness of the Human Resource District, and is also a prerequisite for the title of Engineering in Accounting and Auditing. The Special Examination was made to Gualaquiza 14D04 District San Juan Bosco - Education for the period from January to December 2014, having met the objectives regarding: Evaluate Internal Control System; Determine the degree of efficiency and effectiveness of District Education; Analyze the professional quality Human Resource Institution and job stability. For this purpose, the phases of the Special Review, made the observation visit to the institution to obtain all relevant and important information of the entity, reviewing files and working papers, SWOT was sighted by applying the indicators management and evaluation of internal control system, finding findings by component having real evidence obtained during the implementation of the Special Examination, same as reported in the issuance of the Final Report. Among the main certain conclusions can be established that the absence of the implementation of internal control manual has generated the institution that is not known in depth the gaps and deficiencies in the performance of officials. District Director of Education shall implement mechanisms to ensure the functioning of internal control, for proper monitoring of the effectiveness and efficiency of its servers and its application at all administrative levels, it will become a parameter of performance evaluation and institutional management.